2005
DOI: 10.1002/jcp.20305
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular domain of the IFNaR2 interferon receptor subunit mediates transcription via Stat2

Abstract: We recently demonstrated that IFNaR2, a subunit of the interferon receptor, can be proteolytically cleaved in response to interferon‐alpha and other activators of protein kinase C. Cleavage occurs at multiple sites, via a mechanism similar to that employed by Notch and the Alzheimer's precursor protein, and releases the intracellular domain (ICD). In this study, we demonstrate that the IFNaR2 ICD, when fused to the yeast Gal4 DNA binding domain (Gal4DBD) selectively modulates transcription of four different pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…Irf9 then provides a nuclear localization signal to move the ICD to the nucleus. We have previously shown that ICD-bound Stat2 can modulate transcription via its TAD [22]. While it remains to be determined if the ICD complex does indeed regulate physiological gene expression and whether regulated proteolysis mediates the IFN response, this report further supports the possibility of RIP signaling via an IFN receptor.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Irf9 then provides a nuclear localization signal to move the ICD to the nucleus. We have previously shown that ICD-bound Stat2 can modulate transcription via its TAD [22]. While it remains to be determined if the ICD complex does indeed regulate physiological gene expression and whether regulated proteolysis mediates the IFN response, this report further supports the possibility of RIP signaling via an IFN receptor.…”
Section: Discussionsupporting
confidence: 63%
“…These findings suggested that IFNaR2 might signal by other, non-canonical mechanisms and, indeed, we subsequently found that this subunit of the IFN receptor is proteolytically cleaved in a regulated manner that resembles signaling by other RIP substrates [21]. We also showed that the receptor ICD can modulate transcription via the TAD of the bound Stat2 molecule [22]. Moreover, we have recently demonstrated that IFNaR2 is a substrate for TACE (unpublished data, A. Saleh, P.P.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Stat2 binds the I2-ICD constitutively in a phosphotyrosineindependent manner Saleh et al, 2002]. Since we have also shown that the Stat2 TAD mediates the transcriptional effects of the I2-ICD [El Fiky et al, 2005], it is conceivable that RIP-ed IFNaR2 might control some of the same genes regulated by the canonical JAK-STAT signaling pathway. A comprehensive survey of the genes regulated by the I2-ICD is required to test this hypothesis.…”
Section: Actions Of Cell Surface Receptors In the Nucleusmentioning
confidence: 98%
“…The data from our lab on the transcriptional effects of the I2-ICD has mainly involved testing the effects of Gal4DBD-ICD fusions on Gal4UAS activity [El Fiky et al, 2005]. The I2-ICD, when fused to Gal4DBD, can either activate or repress various reporters linked to a Gal4UAS, possibly dependent on the presence of other transcriptional regulatory elements in the reporter constructs.…”
Section: Actions Of Cell Surface Receptors In the Nucleusmentioning
confidence: 99%